2018
DOI: 10.1111/jopy.12432
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality, perceived competitiveness, and approach‐avoidance motivation

Abstract: Objective Scholars disagree on whether income inequality has incentive or disincentive effects. In the present research, we move beyond such debate and focus on the motivational processes that income inequality predicts. First, income inequality makes economic stratification salient; therefore, it should promote perceived competitiveness. Second, competitiveness can be appraised as both a challenge and a threat; therefore, it should promote both approach and avoidance motivation. Method In three studies (N = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 63 publications
7
120
1
8
Order By: Relevance
“…This study was approved by the Michigan State University Institutional Review Board (IRB#: 00001184: Workplace Interactions and Well‐Being). We recruited participants from ResearchMatch (for a recent example, see Sommet, Elliot, Jamieson, & Butera, ), a website created by Vanderbilt University and funded by the National Institutes of Health Clinical and Translational Science Award. ResearchMatch's purpose is to help match researchers with study participants who have indicated their willingness to be recruited for research studies.…”
Section: Study 2 Methodsmentioning
confidence: 99%
“…This study was approved by the Michigan State University Institutional Review Board (IRB#: 00001184: Workplace Interactions and Well‐Being). We recruited participants from ResearchMatch (for a recent example, see Sommet, Elliot, Jamieson, & Butera, ), a website created by Vanderbilt University and funded by the National Institutes of Health Clinical and Translational Science Award. ResearchMatch's purpose is to help match researchers with study participants who have indicated their willingness to be recruited for research studies.…”
Section: Study 2 Methodsmentioning
confidence: 99%
“…Current psychological approaches suggest that times of economic turmoil and rising social inequality clearly exemplify sources of economic threat that could instigate destructive or potentially negative psychological responses [20]. For instance, recent research indicates that increased income inequality, one of the most distinctive features of the Great Recession [21], may exacerbate social distance between citizens [22], thereby fostering individualistic tendencies [23] and perceptions of interpersonal competitiveness [24]. Nevertheless, research that directly analyzes the links between the experience of personal economic threat related to the economic crisis and theoretically relevant psychological outcomes is limited [25].…”
Section: Perceived Economic Threat and Prosocial Behaviormentioning
confidence: 99%
“…In recent years, economic inequality has been growing in the majority of developed countries (Piketty and Saez, 2014). This inequality is associated with important psychological processes, the most unequal societies tend to promote relational dynamics that are focused on personal independence and individualism (Sánchez-Rodríguez et al, 2018, 2019), competitiveness (Sánchez-Rodríguez et al, 2018; Sommet et al, 2018), and aggressiveness and hostility (Greitemeyer and Sagioglou, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, economic inequality has been found to influence perceived societal norms, leading individuals to infer that others are more individualistic (Sánchez-Rodríguez et al, 2018); it also leads them to describe themselves by means of an independent self-construal (Sánchez-Rodríguez et al, 2019). At the same time, economic inequality is an important predictor of perceived competitiveness within a society (Sánchez-Rodríguez et al, 2018; Sommet et al, 2018). When people perceive that there is a high degree of economic inequality, they tend to be less cooperative with others (Nishi et al, 2015), and high status people become less generous [Côté et al, 2015; but see Schmukle et al (2019) for a non-replication of this finding].…”
Section: Introductionmentioning
confidence: 99%